2022
DOI: 10.1038/s41413-022-00211-2
|View full text |Cite|
|
Sign up to set email alerts
|

FABP4 secreted by M1-polarized macrophages promotes synovitis and angiogenesis to exacerbate rheumatoid arthritis

Abstract: Increasing evidence shows that adipokines play a vital role in the development of rheumatoid arthritis (RA). Fatty acid-binding protein 4 (FABP4), a novel adipokine that regulates inflammation and angiogenesis, has been extensively studied in a variety of organs and diseases. However, the effect of FABP4 on RA remains unclear. Here, we found that FABP4 expression was upregulated in synovial M1-polarized macrophages in RA. The increase in FABP4 promoted synovitis, angiogenesis, and cartilage degradation to exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…In addition, macrophages can secrete a large number of cytokines and differentiate into pro-in ammatory M1 subtypes in the synovitis environment. These cytokines can further lead to joint destruction through neutrophil recruitment and T cell activation [21]. However, early RA is often di cult to diagnose because of its atypical clinical symptoms and lack of speci c serum diagnostic markers [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, macrophages can secrete a large number of cytokines and differentiate into pro-in ammatory M1 subtypes in the synovitis environment. These cytokines can further lead to joint destruction through neutrophil recruitment and T cell activation [21]. However, early RA is often di cult to diagnose because of its atypical clinical symptoms and lack of speci c serum diagnostic markers [22].…”
Section: Discussionmentioning
confidence: 99%
“…Not only mechanical stress, but also synovitis, especially M1 macrophage polarization, received increasing attention [ 45 ]. According to clinical surveys and empirical findings, M1 macrophages are thought to be responsible for OA progression, including osteophyte generation and synovitis [ 46 , 47 , 48 ]. As a result, treatment techniques aimed at reducing the number of M1 macrophages or shifting M1 macrophages to M2 macrophages have been proposed as a way to attenuate OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances revealed that enhancing the expression of PPARg could attenuate disease manifestations (37). The adipokine fatty acid binding protein 4 (FABP4), which is an increased expression in RA serum and synovial tissues (38)(39)(40), plays an important role in the regulation of inflammation. Guo et al found that inhibition of FABP4 expression in macrophages could alleviate RA synovitis, angiogenesis, and cartilage degeneration (40).…”
Section: Discussionmentioning
confidence: 99%
“…The adipokine fatty acid binding protein 4 (FABP4), which is an increased expression in RA serum and synovial tissues (38)(39)(40), plays an important role in the regulation of inflammation. Guo et al found that inhibition of FABP4 expression in macrophages could alleviate RA synovitis, angiogenesis, and cartilage degeneration (40). Studies of transcriptomes of epithelial cell-specific NFIL3 knockout mice showed declined FABP4 expression, suggesting a positive regulatory relationship (41).…”
Section: Discussionmentioning
confidence: 99%